Estudio de un material compuesto a base de fibras Naturales de Cabuya para mejorar las propiedades Mecánicas de elementos de concreto reforzado. - Estrella Charcopa, Stefani Andrea (2016)
The purpose of this study is to contribute with information about the addition of coir fibers at a concrete mix and the application of a FRCM (Fabric Reinforced Cementitious Matrix) composite reinforced with fabrics of natural fibers of cabuya (sisal) as a strengthening system for concrete elements. The physical and mechanical characterization of the materials considered in this thesis was performed in coir fibers, yarns and fabrics of cabuya fibers, and samples of cement mortar and concrete. The concrete was prepared by using pozzolanic portland cement provided by the company "Cemento Chimborazo" and aggregates of the mine "Cerro Negro", located in the province of Chimborazo, whereas samples of composite materials were prepared using a cement portland matrix reinforced with fabrics of cabuya. Furthermore, physical and mechanical properties of the samples of composite material such as, water absorption, absorption by capillarity, density, tensile strength, flexural strength, among others, were evaluated. The tensile and flexural tests were also employed to study the mechanical behavior of the mortar matrix. On the other hand, 3% of straw of coir fibers (volume in weight) was added in concrete samples, fibers that had a length of 5 cm, in order to improve the flexural and/or compressive properties of the concrete. Finally, the results of tests conducted on samples of cylinders and beams of plain concrete, concrete reinforced by coir fibers, concrete reinforced with composite materials, and concrete reinforced with coir fibers and composite materials in terms of their mechanical properties in compression and bending are presented. The results found in this thesis reveal that the samples of concrete reinforced with FRCM composites achieved an improvement in the compressive strength of 6% and concrete samples reinforced with coir fibers and FRCM composites exhibited an improvement of 93% in their flexural strength, in comparison with samples of plain concrete.